Modelling coronary flows: impact of differently measured inflow boundary conditions on vessel-specific computational hemodynamic profiles. (June 2022) - Lodi Rizzini, Maurizio; Candreva, Alessandro; Chiastra, Claudio; Gallinoro, Emanuele; Calò, Karol; D'Ascenzo, Fabrizio; De Bruyne, Bernard; Mizukami, Takuya; Collet, Carlos; Gallo, Diego; Morbiducci, Umberto
Highlights: In vivo measured coronary blood flow rate should be used in personalized CFD simulations Four measurement techniques provided different individual flow rate estimates, propagating uncertainty to CFD-derived coronary hemodynamic profiles Coronary luminal surface area exposed to low WSS is robust to differently measured inlet flow rates Coronary helical flow topology is scarcely sensitive to differently measured inlet flow rates Standardization is needed to use personalized CFD-based WSS profiles in cardiology Abstract: Background and Objectives: The translation of hemodynamic quantities based on wall shear stress (WSS) or intravascular helical flow into clinical biomarkers of coronary atherosclerotic disease is still hampered by the assumptions/idealizations required by the computational fluid dynamics (CFD) simulations of the coronary hemodynamics. In the resulting budget of uncertainty, inflow boundary conditions (BCs) play a primary role. Accordingly, in this study we investigated the impact of the approach adopted for in vivo coronary artery blood flow rate assessment on personalized CFD simulations where blood flow rate is used as inflow BC. Methods: CFD simulations were carried out on coronary angiograms by applying personalized inflow BCs derived from four different techniques assessing in vivo surrogates of flow rate: continuous thermodilution, intravascular Doppler, frame count-based 3D contrast velocity, and diameter-based scaling law. The impact of inflow BCs on coronary hemodynamics was evaluated in terms of WSS- and helicity-based quantities. Results: As main findings, we report that: (i) coronary flow rate values may differ based on the applied flow derivation technique, as continuous thermodilution provided higher flow rate values than intravascular Doppler and diameter-based scaling law (p = 0.0014 and p = 0.0023, respectively); (ii) such intrasubject differences in flow rate values lead to different surface-averaged values of WSS magnitude and helical blood flow intensity (p<0.0020); (iii) luminal surface areas exposed to low WSS and helical flow topological features showed robustness to the flow rate values. Conclusions: Although the absence of a clinically applicable gold standard approach prevents a general recommendation for one coronary blood flow rate derivation technique, our findings indicate that the inflow BC may impact computational hemodynamic results, suggesting that a standardization would be desirable to provide comparable results among personalized CFD simulations of the coronary hemodynamics.